2010
DOI: 10.4049/jimmunol.0901912
|View full text |Cite
|
Sign up to set email alerts
|

Human CD1D Gene Expression Is Regulated by LEF-1 through Distal Promoter Regulatory Elements

Abstract: CD1d-expressing cells present lipid Ag to CD1d-restricted NKT cells, which play an important role in immune regulation and tumor rejection. Lymphoid enhancer-binding factor-1 (LEF-1) is one of the regulators of the Wnt signaling pathway, which is a powerful regulator in cellular growth, differentiation, and transformation. There is little evidence connecting Wnt signaling to CD1d expression. In this study, we have identified LEF-1 as a regulator of the expression of the gene encoding the human CD1d molecule (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 38 publications
0
19
0
Order By: Relevance
“…35 LEF-1 is highly (Image 1A). It has been recently suggested that SMZL and HCL may originate from a circulating IgM+/IgD+/CD27+ B cell derived from the splenic marginal zone that has acquired somatic hypermutations in the absence of germinal center reactions.…”
Section: Discussionmentioning
confidence: 95%
“…35 LEF-1 is highly (Image 1A). It has been recently suggested that SMZL and HCL may originate from a circulating IgM+/IgD+/CD27+ B cell derived from the splenic marginal zone that has acquired somatic hypermutations in the absence of germinal center reactions.…”
Section: Discussionmentioning
confidence: 95%
“…Although LEF1 is best known for its role in WNT/b-catenin signaling, there is evidence that it can also function independent of b-catenin in transcription regulation, and these functions are induced by the HMG domain or by its interaction with alternative cofactors. [28][29][30][31] It will be of great interest to assess these alternative mechanisms of action of LEF1 in chronic lymphocytic leukemia. Recently, several pharmacological inhibitors or small molecules have been shown to efficiently induce apoptosis of chronic lymphocytic leukemia cells in vitro through their interaction with LEF1.…”
Section: Discussionmentioning
confidence: 99%
“…RARa is thought to modulate CD1d expression by altering the activity of LEF-1, a nuclear protein that associates with translocated b-catenin and binds to the distal region of the CD1d promoter. [29][30][31] Furthermore, overexpression of LEF-1 in both K562 and Jurkat human leukemia T-cell lines silences the human CD1d promoter activity, suggesting that higher levels of LEF-1 expression in LCL may also downregulate CD1d expression. 30 Given that EBV transformation of B cells resulted in a loss of CD1d that could be restored with AM580, we hypothesized that CD1d expression in LCL is silenced by the binding of LEF-1/ b-catenin complex to the CD1d distal promoter on EBV infection and that AM580 treatment restores CD1d expression by inhibiting the accumulation of LEF-1 at the CD1d promoter.…”
Section: Blood 10 October 2013 X Volume 122 Number 15 Ebv-infected mentioning
confidence: 99%